Aromatic ring functionalization of benzolactam derivatives: New potent dopamine D3 receptor ligands - Ortega, Raquel; Hübner, Harald; Gmeiner, Peter; Masaguer, Christian F. (Bioorganic & Medicinal Chemistry Letters, 2011)
Since the discovery of the dopamine D receptor, an intensive effort has been directed toward the development of potent and selective ligands in order to elucidate the function and potential therapeutic advantages of targeting D receptors. As a part of our efforts, a novel series of substituted benzolactams derivatives was synthesized mostly through palladium-catalyzed reactions. Their affinities on D -D receptors were evaluated and the data led us to highly potent D ligands, some of them highly selective for D receptor, compared to the related dopamine receptor subtypes. Functional D activity assays of the most relevant compounds have been carried out revealing antagonist as well as partial agonist activity. © 2010 Elsevier Ltd. All rights reserved.